Transition metal-based MOFs for Fenton-like photocatalytic degradation of organic pollutants: Performance, stability, and biocompatibility - S.M. Tikhanova; Yu.A. Tishchenko; E.Yu. Stovpiaga; M. Timofeeva; D.V. Lipin; S.A. Povarov; V.A. Milichko; A.S. Timin; S.A. Shipilovskikh; V.I. Popkov (Environmental Chemistry and Ecotoxicology)
The development of efficient materials for water treatment is crucial to addressing global environmental challenges. In this study, transition metal-based metal-organic frameworks (MeBDC MOFs; Me = Fe, Co, Ni; BDC = benzene dicarboxylic acid) were synthesized via a solvothermal method and considered as dual-function photocatalysts for adsorption and removal of organic pollutant. Comprehensive physicochemical analysis of the developed samples was performed using scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), energy-dispersive X-ray spectroscopy (EDX), fourier-transform infrared spectroscopy (FTIR), raman spectroscopy, N2 adsorption-desorption isotherms (BET), and diffuse reflectance spectroscopy (DRS). The materials exhibited a high visible-light absorption with band gap energies of 1.76 eV (FeBDC), 3.08 eV (CoBDC), and 3.73 eV (NiBDC), BET surface areas of 28.2 m2/g (FeBDC), 74.3 m2/g (CoBDC), and 31.4 m2/g (NiBDC). Photocatalytic performance was evaluated using methylene blue (MB) degradation under visible-light irradiation containing both conventional and Fenton-like processes. FeBDC achieved a reaction rate constant of 0.2719 min−1 with 50 mmol/L H₂O₂, outperforming other materials due to its superior visible-light absorption and catalytic activity, which justified its selection for more detailed mechanistic studies. The proposed mechanism involves ligand-to-metal charge transfer (LMCT) and Fe-driven generation of reactive oxygen species (ROS) such as hydroxyl radicals. In vitro studies conducted on human monocytes (THP-1), murine embryonic fibroblasts (MEF-NF), breast cancer cells (4T1), melanoma cells (B16-F10), and colorectal cancer cells (CT26) demonstrated high biocompatibility of the developed MOFs. By reducing reliance on toxic chemical treatments, this study highlights MeBDC MOFs as highly efficient, biocompatible, and sustainable photocatalysts, with significant potential for industrial and domestic water purification applications.